Effect of Sodium Carboxymethylcellulose and Sorbitol on Anti-Peptic Ulcer Activity of Anredera cordifolia Leaves Extract - Maria Ulfah; Revika Rachmaniar; Egi MR. Sudrajat; Rida W. Fadla; Hary S. Pinuji (Universitas Padjadjaran, Indonesia)
Anredera cordifolia or binahong is one of the Indonesian medicinal plants that is used to treat peptic ulcer. The purpose of this study was to evaluate the effect of the addition of sodium carboxymethylcellulose (CMC) and sorbitol on anti-peptic ulcer activity of A. cordifolia leaves extracts in male Wistar rats. The plants were extracted using decoction method and freeze dried. Three liquid formulas were used i.e., i) a combination of sodium CMC and sorbitol; ii) only sorbitol; iii) extract only. The rats were divided into 6 groups, i.e., positive control (sucralfate 35 mg/kg body weight); negative control (80% ethanol); normal control; and 3 formulas. After the administration of the liquid formula, all groups, except normal control, were given 80% ethanol (l5 ml/kg body weight) to induce peptic ulcer. Antipeptic ulcer activity was evaluated using direct observation on rats gastric mucosa, and histopathology assessment. The result showed that the strongest anti-peptic ulcer was shown by sorbitol only (96.95% inhibition), followed by the combination of sodium CMC and sorbitol (92.68% inhibition). The formula which only contained extract showed only 31.70% inhibition. Statistical analysis showed significant differences between formula 1 and 2 with negative controls. In conclusion, A. cordifolia leaves extract with the addition of sorbitol showed the strongest anti-peptic ulcer activity. Keyword: Anredera cordifolia, peptic ulcer, suspense, Wistar rat.